AVESTODA ETNOGRAFIK MA’LUMOTLARNING AKS ETISHI: ZARDUSHTIYLIK DINI BILAN BOG‘LIQ URF ODAT MA’ROSIMLAR - Avloqulova Charos, Mo’minova Sevinch (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the emergence of the Zoroastrian religion, the history of its founder Zarathushtra, the gods of the Zoroastrian religion, the history of the Holy book of Avesta, and the essence of the book of Avesta.